NANDYAL GRAM 452 (NBEG 452), A HIGH YIELDING DESI CHICKPEA VARIETY FOR ANDHRA PRADESH - V. JAYALAKSHMI*, S. NEELIMA, A.TRIVIKRAMA REDDY, S. KHAYUM AHAMMED N. KAMAKSHI and S. JAFFAR BASHA (The Journal of Research ANGRAU, 2021)
Nandyal Gram 452 (NBeG 452), a high yielding desi chickpea cultivar developed by RegionalAgricultural Research Station, ANGRAU, Nandyal was notified during October, 2020 for commercialcultivation in Andhra Pradesh state. The variety has a yield potential of 2500 kg ha-1 with a durationof 90 – 105 days. It is semi -spreading type with attractive pods and bold seeds having a test weightof 24-26 g and protein content of 20.5 %. This variety has gained attention of the farmers and it haspotential to replace the old variety ‘JG -11’ and is expected to contribute for increase in chickpeaproductivity and net returns in farmers holdings.